Oligosaccharide Shells as a Decisive Factor for Moderate and Strong Ionic Interactions of Dendritic Poly(ethylene imine) Scaffolds under Shear Forces. Issue 27 (27th May 2014) - Tripp, Sandra; Appelhans, Dietmar; Striegler, Christin; Voit, Brigitte
Abstract For better understanding and improving the non‐covalent interactions of dendritic core–shell, we evaluated the interactions of hyperbranched poly(ethylene imine) (PEI) decorated with various oligosaccharide shells with water‐soluble B vitamins, an estradiol derivative and pantoprazole. Depending on the different properties of the analyte molecules, dendritic core–shell glyco architectures showed (very) weak, moderate and strong interactions with the analyte molecules. Thus, ionic interactions are the strongest driving force for the formation of host–guest complexes. The core–shell glyco architecture is a necessary prerequisite for stable analyte/PEI complexes; the pure hyperbranched PEI did not show any sufficiently strong interactions with neutral, cationic or anionic analytes under the shear forces applied during ultrafiltration of pure aqueous solution without an adjusted pH. Thus, only robust non‐covalent interactions between analytes and the dendritic polyamine scaffold of the glycopolymer structure survive this separation step and allow isolation of stable host–guest complexes in aqueous solution.